HYPERTHYROIDISM AND ATRIAL FIBRILLATION - I. M. Marusenko; E. G. Petrova (Столичная издательская компания, 2017)
Review on a problem of the development of atrial fibrillation in patients with thyrotoxicosis is presented. Thyrotoxicosis is one of the most frequent endocrine diseases, conceding only to a diabetes mellitus. The most frequent reasons of hyperthyroidism are Graves' disease and functional thyroid autonomy. The authors give an analysis of data on the cardiac effects of thyrotoxicosis, features of heart remodeling under the influence of thyroid hyperfunction, prevalence of atrial fibrillation in thyrotoxicosis, depending on age, as well as the possibility of restoring sinus rhythm in the combination of these diseases. Particular attention is paid to the effect on the heart of subclinical thyrotoxicosis, which is defined as a dysfunction of the thyroid gland, characterized by low serum concentration of thyrotropin, normal values of free thyroxine and free triiodothyronine. Subclinical hyperthyroidism is also capable of causing heart remodeling and diastolic dysfunction.Prevalence of thyrotoxicosis in elderly people is higher in areas of iodine deficiency; it is relevant for our country due to the large territory of iodine deficiency. In elderly patients, the cardiac effects of thyrotoxicosis prevail in the clinical picture, that makes it difficult to diagnose endocrine disorders, and correction of thyrotoxicosis is critically important for the successful control of the heart rhythm. The article also discusses the problem of thyrotoxic cardiomyopathy, caused by the toxic effect of excess thyroid hormones: features of this heart disorder, factors affecting its formation, clinical significance and contribution to the development of rhythm disturbances. The greatest significance is the development of atrial fibrillation as a result of thyrotox-icosis in older patients who already have various cardiovascular diseases.Atrial fibrillation is the most frequent heart rhythm disorder in thyrotoxicosis. The main cause of arrhythmia in hyperthyroidism is the simultaneous existence of frequent focal impulses and circular motions of the excitation wave - the mechanism re-entry. Successful treatment of atrial fibrillation in patients with thyrotoxicosis is possible only when euthyroidism is achieved. In most cases, after the elimination of thyrotoxicosis, a spontaneous restoration of the sinus rhythm is observed. The chances of sinus rhythm restoration are lower in elderly patients with concomitant organic diseases of the myocardium or long-term atrial fibrillation. Moreover, even radically cured thyrotoxicosis leads to deterioration in the life prognosis.